(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The teaching of business administration was introduced in Spain mainly by private institutions of higher education. These institutions still continue in their task, but they have adapted their procedures according to the changing conditions of the environment. Today these institutions face two new challenges, the adaptation of their programs to the new European higher Education Space and to train qualified professionals in order to upgrade the competitiveness of the Spanish economy.